The chemical constituents of Sterculia comosa (wall) Roxb woods for arginase inhibitory, antioxidant activity, and molecular docking against SARS CoV-2 protein. Issue 1 (January 2022) - Prastiwi, Rini; Elya, Berna; Hanafi, Muhammad; Sauriasari, Rani; Desmiaty, Yesi; Dewanti, Ema; Herowati, Rina
Abstract: Flavonoids and phenols have an arginase inhibitory and antioxidant activity. The Sterculia genus has phenols and flavonoids content. This study aimed to investigate the arginase inhibitory and antioxidant activity of the chemical constituent of Sterculia comosa (wall) Roxb and also their binding affinities to arginase. The most active extract was methanol extract. This active extract was determined for its arginase inhibitory and antioxidant activity, determined the total phenols and total flavonoids, and identified chemical compound. The methanol extract has IC50 2.787 μg/ml for arginase inhibitory activity and IC50 4, 199 μg/ml for DPPH scavenging activity. The total phenols 723.61 mg GAE/gr, total flavonoids content 28.96 mg QE/gr extract. The chemical constituent: KC4.4.6 ((-)-2-(E)-caffeoyl-D-glyceric acid) and KC4.4.5.1 (trans-isoferulic acid) have an arginase inhibitory activity KC4.4.6: 98, 03 μg/ml and KC4.4.5.1: 292, 58 μg/ml. Antioxidant activity with DPPH methods KC4.4.6: 48, 77 μg/ml and KC4.4.5.1: 88, 08 μg/ml. Antioxidant by FRAP methods KC4.4.6: 16, 4 FeEAC mol/g and KC4.4.5.1: 15, 79 FeEAC mol/g. The isolate trans-isoferulic acid predicted has good interaction to arginase. Isolate KC4.4.6. Predicted has good interaction to PLPro of SARS CoV-2 PLpro. However, both isolates did not show good interaction to 3CLPro, nsp12, and Spike protein of SARS CoV-2. Abstract : Arginase; Antioxidant; SARS CoV-2; Sterculia comosa (wall) Roxb.; Molecular docking.